Pengaruh Model Pembelajaran Guided Discovery Learning Terhadap Keterampilan Berpikir Kreatif Siswa Kelas X Pada Materi Struktur Atom Sma Negeri 6 Pematangsiantar - Sipayung, Theresa; Manurung, Hisar Marulitua; Pane, Eva Pratiwi (UNIB Press, 2025)
This study aims to determine the effect of the Guided Discovery Learning model on the creative thinking skills of Class X students in the topic of atomic structure at SMA Negeri 6 Pematangsiantar. The research method used was a quasi-experimental design by comparing an experimental class with a control class. The results showed an improvement in students’ creative thinking skills in the experimental class. This can be seen from the increase in the average pre-test score of 81.25 to the post-test average score of 87.47. Hypothesis testing also supports this finding, where the tcount value of 3.879 is greater than the ttable value of 1.699, and the significance value (2-tailed) of 0.000 is smaller than α (0.05). Therefore, it can be concluded that the Guided Discovery Learning model has a significant effect on students’ creative thinking skills in Class X on the topic of atomic structure.